Hydrothermal Synthesis of α-MnO2 Nanorods and its Electrochemical Characterization for Supercapacitor Applications - Krishnan, Syam G.; Harilal, Midhun; Mohd Hasbi, Ab. Rahim; Rajan, Jose (2016)
MnO2 is considered as a candid material for supercapacitor applications owing to its varied oxidation states, environmental friendliness and low cost. α-MnO2 nanorods is synthesized by a facile hydrothermal method and is characterized by X-ray Diffraction, Field Emission Scanning Electron Microscopy, gas adsorption studies, cyclic voltammetry, Galvanostatic charge-discharge studies and Electrochemical impedance spectroscopy. The α-MnO2 demonstrated a promising specific capacitance of ~310 F g-1 at a current density of 1 A g-1 with lower contact resistance in 3M LiOH